Effect of Thermal-Related Fit Clearance between Outer Ring and Pedestal on the Vibration of Full Ceramic Ball Bearing - Huaitao Shi; Xiaotian Bai; Ke Zhang; Yuhou Wu; Zinan Wang (Shock and Vibration)
Full ceramic bearing can work under a wide range of temperatures, but the thermal deformation difference between the ceramic outer ring and steel pedestal has a great increase with the rise of temperature and leads to obvious impact and friction. In this paper, the thermal deformation difference is considered and the fit clearance is taken as the boundary condition of the dynamic model. Investigations on the dynamic response of the outer ring are conducted, and the effect of thermal-related fit clearance is analyzed at different working temperatures and rotation speeds through parametric study and experiments. Results show that the vibration of the outer ring grows with the temperature and shows different changes with rotation speed as the temperature changes. The variation of working temperature brings difference in the interactions between the outer ring and the pedestal, and the trends of vibration with rotation speed also change at different temperatures. Impact and friction make great contributions to the interactions between the outer ring and the pedestal and show different changes with temperature. This study puts forward a method for the calculation of bearing vibration at variable temperatures and provides theoretical basis for the application of the full ceramic bearings.